2012
DOI: 10.1249/mss.0b013e3182663117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fractionized and Continuous Exercise on 24-h Ambulatory Blood Pressure

Abstract: In prehypertensive individuals, fractionized exercise (e.g., three 10-min aerobic exercise sessions spread and effective exercise alternative to continuous exercise for cardiovascular risk reduction in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
34
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 25 publications
6
34
2
Order By: Relevance
“…Previous studies demonstrating the acute BP-lowering effects of fractionized exercise have used moderate-to-vigorous physical activity. 8,9,12,36 The present results extend these findings by showing that accumulation of very-light-intensity physical activity (~2 METs) can also reduce ABP.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Previous studies demonstrating the acute BP-lowering effects of fractionized exercise have used moderate-to-vigorous physical activity. 8,9,12,36 The present results extend these findings by showing that accumulation of very-light-intensity physical activity (~2 METs) can also reduce ABP.…”
Section: Discussionsupporting
confidence: 86%
“…Sample size calculations to achieve statistical power were based on data from prior research published on physical activity and 24-h ABP reduction. 9 The estimated sample size was 10 participants to detect a 4 mm Hg difference in SBP over 24 h between the walking workstation and control groups (α = .05, β = 0.80). Data were expressed as means ± standard deviation (SD) unless otherwise specified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another component that has received less attention is whether the exercise is performed continuously or cumulatively. Some studies support the idea that accumulated bouts may be a better strategy for prescribing aerobic exercise, by providing greater PEH than continuous bouts (2,5,22,32,33), while others suggested continuous and accumulated acute exercise bouts elicit similar blood pressure reductions (13,27). A question therefore arises as to what could explain these conflicting findings?…”
Section: Introductionmentioning
confidence: 99%
“…Notably, among seven previous studies that directly compared the effects of continuous versus accumulated exercises on PEH, five equated total work from the external work completed (2,5,22,32,33), while two studies employed isocaloric conditions, and concluded that accumulated exercise elicited similar reductions in blood pressure to continuous exercise (13,27). How work is equated is an important methodological issue that confounds the interpretation of studies that compared the acute effects of continuous versus accumulated exercise on PEH.…”
Section: Introductionmentioning
confidence: 99%